Carbon phase adjustment by multi-configuration ligand in endohedral metallofullerene derivatives Gd@C82(morpholine)7 under high pressure. (April 2021) - Yao, Huanli; Yao, Haodong; Huang, Huan; Zhang, Lele; Cui, Rongli; Guo, Xihong; Cheng, Hu; Li, Yanchun; Li, Xiaodong; Gao, Xingfa; Zhao, Lina; Sun, Baoyun
Highlights: We realize the "zoom-in" high pressure analysis of metallofullerenes (Gd@C82 ). The "three-level" phase transition procedure are achieved through morpholine ligand. The carbon cage and morpholine groups are conserved with anisotropic shrinkage. New constructed bonds and the encaged metal's movement is found. The charge-transfer principle is the beneath driving force for the phase transition. Graphical Abstract: ga1 Abstract: Metallofullerenes present an ideal research object for developing new carbon structures with improved properties under high pressure. In this study, high pressure investigation is realized on metallofullerene derivatives (Gd@C82 (morpholine)7 ) by applying in situ synchrotron XRD, Raman, and IR spectroscopy, combined with high pressure density functional theory (DFT) calculations. The regulations of multi-configuration morpholine ligands avoid the direct collapse of the carbon cages commonly happened to fullerenes, making the fine structure transformation possible for the first time, including ligand configuration exchange, anisotropic shrinkage of cage, new constructed bonds, and even the encaged metal's movement with increasing pressure. The charge-transfer principle as the beneath driving force of structural transition is found. These findings demonstrate that multi-configuration ligand maps an innovative strategy for phase transition control of metallofullerenes under high pressure, thus providing deep insight, step by step, into the phase transition mechanism of these hybrid molecular systems on molecular level.